Ecdysone-controlled nuclear receptor ERR regulates metabolic homeostasis in the disease vector mosquito Aedes aegypti - Geng, Dan-Qian; Wang, Xue-Li; Lyu, Xiang-Yang; Raikhel, Alexander S.; Zou, Zhen (PLoS genetics, 2024)
Hematophagous mosquitoes require vertebrate blood for their reproductive cycles, making them effective vectors for transmitting dangerous human diseases. Thus, high-intensity metabolism is needed to support reproductive events of female mosquitoes. However, the regulatory mechanism linking metabolism and reproduction in mosquitoes remains largely unclear. In this study, we found that the expression of estrogen-related receptor (ERR) , a nuclear receptor, is activated by the direct binding of 20-hydroxyecdysone (20E) and ecdysone receptor (EcR) to the ecdysone response element (EcRE) in the ERR promoter region during the gonadotropic cycle of Aedes aegypti (named AaERR). RNA interference (RNAi) of AaERR in female mosquitoes led to delayed development of ovaries. mRNA abundance of genes encoding key enzymes involved in carbohydrate metabolism (CM)— glucose-6-phosphate isomerase ( GPI ) and pyruvate kinase ( PYK )—was significantly decreased in AaERR knockdown mosquitoes, while the levels of metabolites, such as glycogen, glucose, and trehalose, were elevated. The expression of fatty acid synthase ( FAS ) was notably downregulated, and lipid accumulation was reduced in response to AaERR depletion. Dual luciferase reporter assays and electrophoretic mobility shift assays (EMSA) determined that AaERR directly activated the expression of metabolic genes, such as GPI , PYK , and FAS , by binding to the corresponding AaERR-responsive motif in the promoter region of these genes. Our results have revealed an important role of AaERR in the regulation of metabolism during mosquito reproduction and offer a novel target for mosquito control.